From Classroom to Discord: A Hybrid Model for Teaching Critical Listening in EFL Contexts - lestari, kenny shania; Ramadhan, Iqbal; Mubarok, Harir (Institut Agama Islam Negeri Palopo, 2025)
Listening skills are a fundamental component of language proficiency, particularly in higher education where critical listening plays a central role. However, these skills are often underemphasized in traditional teaching contexts, prompting educators to adopt innovative digital platforms. This study explores the implementation of Discord in a hybrid critical listening course conducted throughout a semester within the International Class Program at Maulana Malik Ibrahim State Islamic University of Malang. Grounded in the Integrative Listening Model, the research employed a descriptive qualitative design, utilizing classroom observation checklists, field notes, and Focus Group Discussions (FGDs) with 40 students. The findings indicate that at the comprehension level, the structured and timely distribution of materials through Discord channels enhanced student readiness and engagement. At the interpretation level, features such as video conferencing, breakout rooms, and audiovisual resources facilitated deeper understanding, allowing students to make inferences more effectively. At the evaluation level, real-time interaction and feedback during discussions supported critical analysis of content. Notably, student performance showed observable improvements in critical listening tasks, as reflected in increased participation rates and higher quality of responses in listening assessments. Despite occasional technical issues like unstable internet connections. The hybrid model which integrated synchronous and asynchronous learning, proved adaptable and effective. The study concludes that Discord, when aligned with a well-structured instructional design and supported by the Integrative Listening Model, can significantly promote critical listening competence in higher education. Future research may examine comparative effectiveness across different digital platforms and explore long-term impacts on listening proficiency development.